Reliability and Validity of an Adapted Arabic Version of the Scoliosis Research Society-22r Questionnaire. Issue 17 (1st September 2015) - Haidar, Rachid K.; Kassak, Kassem; Masrouha, Karim; Ibrahim, Kamal; Mhaidli, Hani
Abstract : Study Design: Cross-sectional validation and reliability assessment study of Arabic version of Scoliosis Research Society-22 (SRS-22r) Questionnaire. Objective: To develop and validate the Arabic version of the SRS-22r questionnaire. Summary of Background Data: The diagnosis and treatment of adolescent idiopathic scoliosis may influence patient quality of life. SRS-22r is an internationally validated questionnaire used to assess function/activity, pain, self-image, and mental health of patients with scoliosis. It has been translated into several languages but not into Arabic language. Therefore, a valid health-related quality-of-life outcome questionnaire for patients with spinal deformity is still lacking in Arabic language. Methods: The English version of SRS-22r questionnaire was translated, back-translated, and culturally adapted to Arabic language. Then, 81 patients with idiopathic adolescent scoliosis were allocated randomly into either the reliability testing group (group 1) or the validity testing group (group 2). Group 1 patients completed Arabic version of SRS-22r questionnaire twice with 1-week interval in-between. Cronbach α and intraclass correlation coefficient were measured to determine internal consistency and temporal reliability. Group 2 patients completed the Arabic version of SRS-22r questionnaire and the previously validated Arabic version of 36-Item Short Form Health Survey (Short Form-36) questionnaire concurrently, and Pearson correlation coefficient was obtained to assess validity. Results: Content analysis, internal consistency reliability, test/retest reproducibility (intraclass correlation coefficient range: 0.82–0.90), and test of concurrent validity showed satisfactory results. Function/activity and satisfaction with management domains had a lower Cronbach α (0.58 and 0.44, respectively, vs . 0.71–0.85 range for others). Self-image/appearance and satisfaction with management had a lower correlation with domains of the 36-Item Short Form Health Survey. Conclusion: An Arabic version of the SRS-22r questionnaire has been developed and validated. This questionnaire will aid health care workers and researchers in evaluation of patient perception of the deformity, satisfaction with treatment, and quality of life in Arabic-speaking populations. Level of Evidence: 3 Abstract : Supplemental Digital Content is Available in the Text.The Scoliosis Research Society-22 (SRS-22r) questionnaire was translated and adapted to Arabic and then tested in a group of 81 patients with idiopathic scoliosis. Cronbach α and intraclass correlation coefficient analyses showed good reliability and reproducibility. Comparison with 36-Item Short Form Health Survey questionnaire revealed its good validity.